Health Risk Assessment of Organochlorine and Synthetic Pyrethroid Pesticide Residues via Dietary Intake of Field grown Fruits and Vegetables - Suleiman, Fanika; A Nuhu, Abdulmumin; Z Yashim, Israila (Nigerian Journal of Pharmaceutical and Applied Science Research, 2021)
Background: The presence of pesticide residues in agricultural products raises serious health concerns for consumers, and consumption of pesticide contaminated vegetables and fruits pose a major threat to public health. The aim of this study was to assess the health risk of organochlorine and synthetic pyrethroid pesticide residues via dietary intake of field grown fruits and vegetables along River Galma in Zaria Kaduna state. Methods: Samples were analysed for multi- pesticide residues using Gas Chromatography-Mass Spectrometry (GC – MS). The health risk indices (HRI) of the pesticide residues via dietary intake of vegetables and fruits were assessed according to the guidelines recommended by the USEPA, where the estimated daily intake (EDI) were compared with the acceptable daily intake (ADI). Results:The human health risk assessment in all the samples analysed revealed that detected organochlorines pesticides such as heptachlor epoxide B, endosulfan II and delta- BHC can pose a threat to human health as they all have HRI values greater than one. Also, a – Cypemethrin, a synthetic pyrethroid with values of 1.01 and 1.86 in spinach and onion respectively greater than index of one. The highest health index values of 26.58, 23.22, and 6.93 were found for heptachlor epoxide B in onion, spinach and carrots respectively. However, some of the detected pesticides pose no health risk in the fruits and vegetables samples analysed. Conclusion: Therefore, the results of this study suggest continuous monitoring and strict regulation of pesticide residues in vegetable and fruits to protect consumer health in the study area.